Minimization of the spherical aberration coefficients of composed of quadrupole and octupole lenses using the rectangular field distribution model - Fatma N. Gaafer (Al-Qadisiyah Journal of Pure Science, 2017)
The optimization calculations are made to find the optimum of the spherical aberration coefficients due to octupole presented. The latter can be combined with the quadrupole lens. The equations are given for composed lenses in the approximation of rectangular model of the field distribution. From the calculations it is found that the spherical aberration coefficients can be reduced to negative value. These results are similar to the results published by Fishkova, T. Ya. and Yavor, S. Ya.(1968) where the negative and positive values are at the found but the present results are the best to give rise to minimum spherical aberration coefficient. These computations have been concentrated on determined the spherical aberration coefficients in both convergence and divergence planes, and also the effects of changing the excitation of lens, the coefficient (Î³) and the effective length of lens "L"(geometrical dimensions) with the changing of object and image distances studied and are taken into account.